ISLAMIC MESSAGES IN THE SASAK TEMBANG TRADITION IN SEMOYANG VILLAGE, WEST NUSA TENGGARA - M. Wahdian Rijalil Hadi; Mohammad Alawi (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2023)
In this era of modernization, the Tembang tradition has declined due to the lack of young people interested in learning to read palm leaves. some people also perceive the Tembang tradition as only conveying entertainment messages without any Islamic elements. The method used is library research with the content analysis approach. The results showed that the Islamic message in the Sasak song tradition in Semoyang village is a message to preach, moral messages, divinity, and the message of parents' will to their children. The Tembang tradition is a medium for delivering da'wah messages in the form of chanting beautiful verses in which there are many messages contained, not only about da'wah, and divinity, but messages that will become the foundation of life.